Characterization of nano-structural and nano-mechanical properties of osteoarthritic subchondral bone. Issue 1 (December 2016) - Zuo, Qiliang; Lu, Shifeier; Du, Zhibin; Friis, Thor; Yao, Jiangwu; Crawford, Ross; Prasadam, Indira; Xiao, Yin
Abstract Background Although articular cartilage is the primary tissues affected by osteoarthritis (OA), the underlying subchondral bone also undergoes noticeable changes. Despite the growing body of research into the biophysical and mechanical properties of OA bone there are few studies that have analysed the structure of the subchondral sclerosis at the nanoscale. In this study, the composition and nano-structural changes of human osteoarthritis (OA) subchondral bone were investigated to better understand the site-specific changes. Methods OA bone samples were collected from patients undergoing total knee replacement surgery and graded according to disease severity (grade I: mild OA; grade IV: severe OA). Transmission electron microscopy (TEM), Electron Diffraction, and Elemental Analysis techniques were used to explore the cross-banding pattern, nature of mineral phase and orientation of the crystal lattice. Subchondral bone nano-hydroxyapatite powders were prepared and characterised using high resolution transmission electron microscopy (HR-TEM) and fourier transform infrared spectroscopy (FTIR). Subchondal bone mechanical properties were investigated using a nano-indentation method. Results In grade I subchondral bone samples, a regular periodic fibril banding pattern was observed and thec -axis orientation of the apatite crystals was parallel to the long axis of the fibrils. By contrast, in grade IV OA bone samples, the bulk of fibrils formed a random and undulated arrangement accompanied by a circular oriented pattern of apatite crystals. Fibrils in grade IV bone showed non-hierarchical intra-fibrillar mineralization and higher calcium (Ca) to phosphorous (P) (Ca/P) ratios. Grade IV OA bone showed higher crystallinity of the mineral content, increased modulus and hardness compared with grade I OA bone. Conclusions The findings from this study suggest that OA subchondral sclerotic bone has an altered mineralization process which results in nano-structural changes of apatite crystals that is likely to account for the compromised mechanical properties of OA subchondral bones.